Basophil activation test for Staphylococcus aureus enterotoxins in severe asthmatic patients. Issue 4 (12th November 2020) - Flora, Martina; Perna, Francesco; Abbadessa, Salvatore; Garziano, Federica; Maffucci, Rosalba; Maniscalco, Mauro; Mollica, Mariano; Pelaia, Corrado; Tremante, Eugenio; Maffei, Marianna; Calabrese, Cecilia
Abstract: Background: Several studies have shown an association between severe asthma and serum immunoglobulins E (IgE) against Staphylococcus aureus enterotoxins (SEs). SEs—the prototypes being types A (SEA), B (SEB) and toxic shock syndrome toxin 1 (TSST‐1)—can induce both polyclonal and specific IgE responses. Objective: The aim of the study was to evaluate the ability of SEs to induce basophil activation in severe asthmatic patients using the basophil activation test (BAT). Methods: 57 severe asthmatic patients were enrolled. BAT in response to SEA, SEB and TSST‐1 was performed in all patients, while serum IgE to SEA, SEB and SEC was available in 49 patients. BAT was considered positive when CD203c+ basophils to SEs were ≥5%, and the stimulation index (SI, ratio between % of CD203c+ basophils to SEs and to negative control) was >2. Two threshold values (>0.1 kU/L and >0.35 kU/L, respectively) were used to assess serum SEsIgE. Results: 36.8% of severe asthmatic patients had a BAT positive for at least one SE (BAT SEs+). Serum SEsIgE >0.35 kU/L (SEs IgE+) was associated with BAT SEs positivity. Among patients with negative skin prick test, 35% were BAT SEs+, 30% SEs IgE+, 55% BAT or IgE− SEs+. A negative correlation between SI of BAT to SEs and both clinical (ACT score) and functional parameters was observed, together with a positive correlation of BAT with asthma exacerbations. Conclusions: The positivity of BAT for SEs in a subgroup of severe asthmatic patients further supports the pathogenic role of Staphylococcus aureus in severe asthma.